Hallyu stars mediated fandom: understanding mediatisation of non-K-Pop consumption among Malaysian youth - Nurul Akqmie Badrul Hisham, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Tapping into mediatisation as a critical lens to examine how cultural synergy, particularly Korean Wave’s influence, manifests and impacts of everyday cultural practice in Malaysia. Despite a delayed start compared to neighbours, the Korean Wave ignited by the drama “Winter Sonata” in 2002, maintains a remarkable popularity in Malaysia. This study delves deeper than the surface of the Korean Wave, or Hallyu, exploring the intricate interplay between Korean stars, social media, and the phenomenon’s power. This work aims to understand how these elements actively shape and maintain its influence. While there has been a proliferation of research on the Korean Wave, it focuses on K-Pop music and K-Drama. Thus, this research project is designated to highlight elements other than K-Pop and K-Drama in the Korean Wave phenomenon by focusing on non-K-Pop cultural products. By observing open social media accounts and content, as well as events related to South Korean products, this study will use qualitative methods, netnography and participant observation for data collection. The findings are discussed in four key themes: Exploring Platforms and Fan Communities and Their Impact on Everyday Practices; International Brands Using Korean Stars for Product Promotion in Malaysia; the Potential of Selected Qualitative Methods for Understanding Social Phenomena; and the Limitations of These Methods in Research. The study highlights the need to choose relevant theories and research methods to improve the quality and depth of findings, especially when exploring complex subjects such as fandom.